2014
DOI: 10.4269/ajtmh.13-0391
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in the Correlation of Antibody and T-Cell Responses to Trypanosoma cruzi

Abstract: Abstract. Chagas disease, caused by the protozoan parasite Trypanosoma cruzi, is a major cause of morbidity and mortality in Central and South America. Geographic variations in the sensitivity of serologic diagnostic assays to T. cruzi may reflect differences in T. cruzi exposure. We measured parasite-specific T-cell responses among seropositive individuals in two populations from South America with widely varying antibody titers against T. cruzi. Antibody titers among seropositive individuals were significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Similarly, low sensitivities of recombinant antigen ELISA and rapid tests have also been reported from Panama [262,263] and Mexico [264] . No clear correlation between serodiagnostic test reactivity and local T. cruzi DTU has been observed; instead, these discrepancies may reflect weaker adaptive immune responses to parasite antigens between endemic populations [265] .…”
Section: T Cruzi Lineage In Chagas Disease Diagnostics and mentioning
confidence: 97%
“…Similarly, low sensitivities of recombinant antigen ELISA and rapid tests have also been reported from Panama [262,263] and Mexico [264] . No clear correlation between serodiagnostic test reactivity and local T. cruzi DTU has been observed; instead, these discrepancies may reflect weaker adaptive immune responses to parasite antigens between endemic populations [265] .…”
Section: T Cruzi Lineage In Chagas Disease Diagnostics and mentioning
confidence: 97%
“…Figure 1 illustrates the diagnostic process used by the CECD in Los Angeles, which has screened over 8000 people in the U.S. for T. cruzi since 2007. Assays have shown varying performance characteristics in different settings and patient populations [ 25 ], which may be due to T. cruzi genetic diversity [ 26 ] and/or geographically patterned variations in immune responses [ 27 ]. This is an especially critical point in light of the heterogeneous nature of the Latin American-origin population in the U.S. A World Health Organization comparative evaluation provides performance characteristics for several assays based on a multinational panel [ 23 ], while a recent meta-analysis includes summary estimates of sensitivity and specificity for both the Wiener Chagatest ELISA (93.7 and 99.0%, respectively) and the Ortho T. cruzi ELISA (99.2 and 99.1%, respectively).…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…Diagnosis of T. cruzi infection has not hitherto been lineage-specific. The search for a TcIspecific antigen applicable to animals and humans remains an important current research goal, and may elucidate the reported differences in serological and immune responses in regions endemic for different lineages [44][45][46].…”
Section: Discussionmentioning
confidence: 99%